Strengthening Digital Entrepreneurial Mindsets And Affiliate Marketing Practices Toward Women Economic Independence In Kebumen - Siti Barokah (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This community service aims to enhance women's digital literacy and entrepreneurial mindset through affiliate marketing training to foster economic independence. Method: A participatory approach was employed at the PKK Building, Kebumen, involving counseling, interactive discussions, and hands-on practice with affiliate platforms and social media promotion. Practical Applications: Findings demonstrate that affiliate marketing offers accessible income opportunities for women and MSMEs with minimal capital, enabling flexible home-based enterprises through digital platforms. Conclusion: Participants exhibited improved understanding of digital entrepreneurship, increased self-confidence, and practical skills in affiliate marketing, indicating that targeted digital literacy interventions can effectively empower women economically in the digital transformation era.